Realization of Optimal FBG Band–Pass Filters for High Speed HDWDM - Ozoliņš, O.; Ivanovs, Ģ. (Elektronika ir Elektrotechnika, 2009)
The influence on FBG filters with different apodization profiles on WDM systems is evaluated numerically with OptSim 5.0 and FBGS 2.6 simulation programs at data transmission rate of 2.5 Gbit/s and 10.52 Gbit/s using 40 km of optical fiber. The realization of low insertion loss optical filter is one of key elements to ensure high speed dense WDM system and FBG filter with different apodization profiles influence on high speed dense WDM is enormous. Ill. 8, bibl. 5 (in English; summaries in English, Russian and Lithuanian).